Development of a clinical quality registry for percutaneous coronary intervention among coronary heart disease patients in Northern Vietnam: A pilot registry study - Vu, Thi Thanh Hoa (Curtin University, 2021)
Cardiac interventional procedures have been used widely for treatment of acute coronary heart disease in developing countries, however, information on quality and safety from everyday clinical practice remains limited. This thesis developed a pilot clinical quality registry to understand the patient profiles, outcomes post procedure and in-hospital cost of patients undergoing percutaneous coronary intervention in Vietnam. Results revealed that despite the high cost, this procedure has been used in high volume and outcomes were positive.